COVID-19 PANDEMIC AND WORLD CAPITAL MARKETS: A REVIEW - Jabeen, Madiha; Malik, Faiza Faiz; Jabeen, Aisha (The journal of contemporary issues in business and government, 2021)
Since 2019 the world is exposed to one of the deadliest pandemics of all times. As Covid-19 hit the nations in every possible way, the global financial markets got exposed to this shock as well. This paper reviews the effects of Covid-19 on financial markets of China and other Asian countries along with its impact on financial markets from rest of the world. World health Organization declared Covid-19 as a pandemic on 11th March 2020 because of its severity and worldwide spread. The stock markets of China and other Asian countries observed a significant downfall. The investor responses were reflected in the fluctuations of stock prices. In China, the notable industries that got badly affected by the pandemic were transportation, catering, mining, agriculture and accommodation. However, the better performance of some sectors helped the stock markets like education, information technology and health in particular. The financial markets of emerging economies and developing countries also suffered badly due to Covid-19. Besides China, other prominent nations that were hard hit by the pandemic include America, United Kingdom, Italy and Spain. One of the possible reasons for negative returns in European markets was the high media coverage related to Covid-19 that led to adverse investor sentiments and decline in market. Secondly, when the pandemic started the European countries announced lockdown at a very initial stage due to which all the economic activities shut down hence resulting into a decline in the market. However, some countries remained quite successful in controlling the virus namely Taiwan, New Zealand, South Korea and Hong Kong.